2017
DOI: 10.1016/j.amjms.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bone Metabolic Markers With Diabetic Retinopathy and Diabetic Macular Edema in Elderly Chinese Individuals With Type 2 Diabetes Mellitus

Abstract: Background Diabetic retinopathy (DR) is a common and specific microvascular complication of diabetes. The association of bone metabolic markers with the risk of DR and diabetic macular edema (DME) is unclear. Materials and Methods We investigated the association between bone turnover markers commonly examined in a clinical setting and DR and DME risk in elderly Chinese patients with type 2 diabetes mellitus (T2DM). A total of 408 patients aged 55 to 70 years old with T2DM were included. We first performed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Consistent with these findings, in a recent study using a health claims database, lipid-lowering medication use was associated with a decreased incidence of DME [6]. Other potential systemic risk factors for DME include age, sleep apnea, pregnancy, anemia, lack of glycemic control, duration of diabetes, nephropathy/microalbuminuria, systemic fluid retention in congestive heart failure or renal disease, and use of the glitazone (thiazolidinedione) class of oral antihyperglycemic medications [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 61%
“…Consistent with these findings, in a recent study using a health claims database, lipid-lowering medication use was associated with a decreased incidence of DME [6]. Other potential systemic risk factors for DME include age, sleep apnea, pregnancy, anemia, lack of glycemic control, duration of diabetes, nephropathy/microalbuminuria, systemic fluid retention in congestive heart failure or renal disease, and use of the glitazone (thiazolidinedione) class of oral antihyperglycemic medications [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 61%
“…In a study that enrolled elderly Chinese patients with T2DM, β-CTX was significantly associated with DME only in females and not related to DR among all individuals. 35 The contradiction might be in part owing to a relatively smaller sample size or varying study population of a wider range of age in the current study. A clinical study documented a positive association between β-CTX and HbA1c in women with normal glucose tolerance, suggesting that bone may serve as a protective compensatory mechanism against subtle increases in HbA1c until the development of diabetes.…”
Section: Discussionmentioning
confidence: 75%
“…On the contrary, some studies showed that no differences were noted between patients with DR and their controls. 34,35 However, serum P1NP was found to be lower in patients with diabetic macular edema (DME). 35 Nevertheless, we did not find significant differences between mild and severe DR stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations